FOXP3 gene expression in multiple sclerosis patients pre- and post mesenchymal stem cell therapy - Mohajeri, Maryam; Farazmand, Ali; Mohyeddin Bonab, Mandana; Nikbin, Behrooz; Minagar, Alireza (Iranian journal of allergy, asthma, and immunology, 2011)
Multiple Sclerosis (MS) is an inflammatory demyelinating and neurodegenerative disorder of the central nervous system (CNS), which mainly affects young adults. Activated T lymphocytes promote the neuro-inflammatory cascade of MS by secreting pro-inflammatory cytokines and play a significant role in its pathogenesis. T lymphocytes may trigger the inflammation, which in turn leads to axonal loss and neurodegeneration observed in the course of MS. Currently, there is no cure for MS, however, one of the most promising neuroprotective research tools consists of the use of bone marrow derived mesenchymal stem cells (MSC). This method promotes immune system regulation and possibly induces neurological repair and re-myelination of the damaged axons. Recent studies have shown that MSC exert an immune regulatory function and induce T regulatory-cell proliferation, therefore, it may serve as a potentially useful treatment for immune-mediated diseases such as MS. In this pilot study a group of MS patients underwent MSC therapy and we assayed the expression of an X-linked transcription factor, FoxP3, as a specific marker of T Regulatory cells in peripheral blood, prior to and after the treatment. Using q RT-PCR for measurement of expression of FoxP3 by peripheral blood mononuclear cells, we found that in all subjects, except for one, the expression of FoxP3 at 6 months after intrathecal injection of MSC was significantly higher than the levels prior to treatment. Such significant enhanced expression of FoxP3 associated with clinical stability. Findings from this pilot study further support the potential of bone marrow derived MSC for treatment of MS patients.